Lessons Learned from Systematic Review for Circular Economy Adoption in the Indonesian Construction Industry - Hidayah, Fitri Nur; Wimala, Mia (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2024)
As population growth continues, so does consumption and the need for basic human necessities, necessitating ongoing development. This development process often relies on non-renewable resources, generates waste, and emits harmful gases, usually neglecting sustainability. The Circular Economy (CE) concept can be applied to support sustainability in the construction industry. This regenerative system replaces the linear economy, focusing on optimizing material utilization and value throughout the product lifecycle and reducing waste generation. Through a Systematic Literature Review based on the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines, this research provides an overview of CE practice trends that the construction industry in Indonesia can adopt based on lessons learned from other countries. The results indicate that CE implementation in Indonesia is highly relevant and important for supporting sustainability from economic, environmental, and social perspectives. To achieve these benefits, Indonesia must overcome various barriers, including less supportive policies, low consumer demand, limitations in the supply chain, and technological and infrastructure constraints. The CE principles commonly applied by the Indonesian construction industry in waste are reduction, reuse, and recovery. To ensure the successful implementation of CE in the construction sector, the Indonesian construction industry can learn from the best CE practices implemented in other countries and adopt effective and efficient strategies to achieve sustainability. However, successful implementation requires commitment and collaboration from various stakeholders, including the government, industry, and academia.